Is there correlation between polymerization shrinkage, gap formation, and void in bulk fill composites? A μCT study - Lauber José dos Santos Almeida Junior; Karla Janilee de Souza Penha; Ana Ferreira Souza; Estevam Carlos Oliveira Lula; Fernando Cintra Magalhães; Darlon Martins Lima; Leily Macedo Firoozmand (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: This in vitro study aimed to evaluate the volume of polymerization shrinkage (VS), gap (VG), and void (VV) using computerized microtomography (μCT) in bulk fill resin composites and conventional class I restorations, and to establish a correlation between these factors. Class I cavities (4 x 5 x 4 mm), C-factor = 4.2, were performed on caries-free human third molars and randomly divided into five groups (n = 6): FSI (Filtek Supreme XTE incremental insertion); FSS [(Filtek Supreme XTE single insertion(SI)]; TBF [(Tetric Bulk Fill: SI and manual filling (MF)]; SFM (Sonic Fill: SI/MF); and SFS (SonicFill: SI and sonic filling). The teeth were scanned and analyzed by μCT at T0, after filling the cavity with resin, and at T1, after polymerization for VG and VV, and for VS (T1-T0). There was statistically significant difference in VS in μCT for the FSI and FSS groups and between SFS and FSS as well as some difference in VV for FSI and bulk fill resin composites and no difference in VG between the conventional technique and bulk fill composites. Bulk fill resin composites presented similar VS and gap formation to those of incrementally inserted conventional resin composites. There is a moderate and weak positive correlation between polymerization shrinkage and gap formation and void, respectively. The final gap formation was more dependent on the initial gap than on polymerization shrinkage or void volume.